Kondiloma Akuminata pada Kehamilan: Tinjauan Kasus dan Tatalaksana - Andriana, Risa; Zulfadli, Zulfadli (Medula, 2024)
Condyloma acuminata (CA) or genital wart is a benign proliferative epidermal or mucosal lesions attributed mostly to HPV type 6 or 11. CA is reported to occur frequently in pregnant women. Management of CA in pregnancy requires consideration of the appropriate benefit and safety ratio. Although there are no standard guidelines for the management of CA in pregnancy, there are several options including cryotherapy, topical imiquimod, laser therapy, photodynamic therapy, trichloracetic acid, and local hyperthermia. This case review aims to demonstrate the effectiveness of KA therapy in pregnancy. The case of a 30 years-old woman with a gestation age of 34 weeks went to RSUD Dr. H. Abdul Moeloek, Lampung Province with multiple verrucous vegetation lesions on vulva and perianal area. The patient was diagnosed with anogenital condyloma acuminata. The patient was treated with 80% TCA once per week until term of pregnancy and the CA lesions were reduced. The patient gave birth by Caesarean Section (SC) to avoid the risk of transmitting viral infections to the baby being born and postpartum electrosurgery was performed on the remaining CA lesion. In conclusion, the management of CA in pregnancy requires several considerations, including gestational age, location and size of the lesion, and potential risks and benefits of therapy.